Bio-modification approach for novel dentine caries management by Galla chinesis extract and microbial transglutaminase - Meng Deng; Xin Xu; Jiyao Li; Xuedong Zhou (Wolters Kluwer Medknow Publications, 2012)
Introduction: Dental caries still remains one of the most prevalent diseases worldwide. Unlike enamel caries which can be restored mainly by modulating mineral balance, the dentine caries are characterized with irreversible proteolytic disintegration of organic matrices, highlighting an urgent need to seek novel management strategies. Bio-modification of dentine matrix has been proposed as a novel and alternative approach to enhancing its biochemical and biomechanical properties. The resultant chemical stability and mechanic durability are specifically desirable for prevention and restoration of dentine caries. However, conventional cross linking agents, e.g. glutaraldehyde, formaldehyde,are unsuitable for clinical use due to marked cytotoxicity or instability over time. The Hypothesis: Previous studies revealed that Galla chinesis extract (GCE) could inhibit cariogenic microbes and positively modulate enamel de/remineralization balance, and the mechanism was directed to the polyphenols-organic matrix interaction involving hydrogen, covalent, ionic bonding and hydrophobic processes. Microbial transglutaminase (mTGase) could induce crosslinks between peptide chains and improve functional properties of food proteins by catalyzing an acyl transfer reaction through ε - (γ-glutamyl) lysine (GL bonds). Given the high organic content in dentine and universal reaction nature of GCE and mTGase, we put forward a hypothesis that these two natural products may serve as novel biocompatible bio-modifiers to improve biochemical and biomechanical properties of dentine matrices. Evaluation of the Hypothesis: The validation of our hypothesis will provide profound insights updating current therapeutic strategies against dentine caries, and pioneer novel approaches for biocompatible bio-modification of dentine matrices. Specifically, GCE and mTGase can be integrated into the root canal irrigating and dentine boding procedures, where they may generate beneficial effects on preservation of integrity of dentine as well as dentine-sealer interface.